A functional variant in the 5′‐flanking region of the chicken serotonin transporter gene is associated with increased body weight and locomotor activity. (10th July 2014) - Phi‐van, Loc; Holtz, Marlis; Kjaer, Joergen B.; van Phi, Valerie D.; Zimmermann, Katrin
Abstract In this study, we identified a polymorphism in the 5′‐flanking region of the chicken serotonin transporter (5‐HTT) gene. Sequencing analysis revealed that in comparison with the wild‐type variant (W), a deleted variant (D) is generated by deletion of four nucleotides (5′‐AATT‐3′) and a single nucleotide change (A→T). Using a polyacrylamide gel electrophoresis system, we found that the 360‐bp DNA fragment containing the W variant with the wild‐type sequence 5′‐AATTAATT‐3′ shows intrinsic DNA curvature while the 356‐bp fragment containing the D variant lacking the four base pairs AATT is not curved. Quantitative real‐time RT‐PCR and ELISA demonstrated that the expression of 5‐HTT in D/D chickens was higher than that in W/W and W/D chickens. In addition, transient transfection experiments with chloramphenicol acetyltransferase reporter gene constructs revealed increased 5‐HTT promoter activity mediated by the D variant and a silencer activity of the W variant. Interestingly, females and males with D/D genotype showed significant greater increase in body weight from 6 weeks and 16 weeks of age, respectively, and higher body mass index. Moreover, we found that D/D chickens of both genders were physically more active than W/W and W/D chickens.<boxed-text content-type="graphic" id="jnc12799-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text> We identified a polymorphism in the 5'‐flanking region of the chicken serotonin transporter (5‐HTT) gene. The expression of 5‐HTT in D/D chickens was higher than that in W/W and W/D chickens. D/D females showed significant greater increase in body weight from 6 weeks of age, higher body mass index and higher content of intra‐abdominal fat. The presence of D/D alleles resulted in increase in physical activity.